Afro-descendant Social Identity in the 21st Century - Colín Rodea, Marisela (2025)
The aim of this paper is to identify and compare the conceptual features of the term afro-descendant social identity in the works of three contemporary authors: Brazilian writer Jeferson Tenório, Mexican Afro-Japanese Chicana pocha writer Jumko Ogatta Aguilar, and Ecuadorian poet from Esmeraldas, Yuliana Ortiz Ruano. To achieve this, a corpus was formed using literary excerpts from each author’s work in which the process of awareness or understanding of identity is described, either by the author or through their characters. The theoretical-methodological framework of the study is ethnographic in nature and was approached as a comparativeanalysis exercise. This allows for an exploration of the ways in which identity is named, sought, or demanded in the 21st century. The paper assumes that afro-descendant social identities are constructed based on characteristics unique to the 21st century, such as transmigration, superdiversity, racialization, empowerment, and the gaze of the Other. However, it also emphasizes that in the Global South, historical processes of colonization, slavery, and decolonization are the result of social struggles, intellectual movements of resistance, and new narratives of defiance that expose various forms of violence—both physical and symbolic.